Evaluation of antibodies against glycoprotein D (gD) and glycoprotein G (gG) in HSV-1 infected individuals' serum samples - Meshkat, Z.; Roostaee, M.N.; Soleimanjahi, M.; Zandi, K. (2012)
Background and Objectives: Glycoproteins D (gD) and G (gG) of herpes simplex virus type 1 (HSV-1) are virus envelope glycoproteins that are able to induce HSV-1 antibody production in infected persons. Therefore, those proteins could be in interest to develop the serodiagnostic test(s) for HSV antibody detection. The aim of present study was the comparison of anti-gD and anti-gG antibodies in HSV-1 infected individuals serum samples. Materials and Methods: In this study, recombinant gD and gG were prepared and used for western blot test to detect the antibodies against HSV-1. Results: Our data showed the total gD antibody titer was higher than gG antibody titer in the HSV-1 infected patient's sera but the gG antibody titer was high significantly. Conclusions: According to our results, gD and gG can be used for designing the diagnostic laboratory tests to evaluate total antibody against HSV-1 and HSV-2.